Vascular geometry as a risk factor for non-penetrating traumatic injuries of the aortic arch. - Andreas Schicho; Lukas Luerken; Christian Stroszczynski; Ramona Meier; Andreas G Schreyer; Lena-Marie Dendl; Stephan Schleder (PLoS ONE)
Purpose To assess biomechanical factors in aortic arch geometry contributing to the development of non-penetrating aortic arch injury (NAAI) in multiply injured patients with an Injury Severity Score (ISS) ≥ 16. Material and methods 230 consecutive multiply injured trauma patients with an ISS ≥ 16 admitted to our Level-I trauma center during a consecutive 24-month period were prospectively included of whom 13 presented with NAAI (5.7%). Standardized whole-body CT in a 2x128-detector-row scanner included a head-and-neck CTA. Aortic arch diameters, width, height, angles and thoracic width and height were measured in individuals with NAAI and ISS-, sex-, age-, and trauma mechanism-matched controls. Results There was no difference between groups regarding sex, age, ISS, and aortic diameters. The aortic arch angle in individuals with NAAI (71.3° ± 14.9°) was larger than in healthy control (60.7° ± 8.6°; p*<0.05). In patients with NAAI, the distance between ascendent and descendent aorta was larger (5.2 cm ± 1.9 cm) than in control (2.8 ± 0.5 cm; ***p<0.001). The aortic arch is higher above tracheal bifurcation in NAAI (3.6 cm ± 0.6 cm) than in matched control (2.4 cm ± 0.3 cm; ***p<0.001). Accordingly, the area under the aortic arch, calculated as half of an eliptic shape, is significantly larger in patients with NAAI (15.0 cm2 ± 6.5 cm2) when compared to age- and sex-matched controls without NAAI (5.5 cm2 ± 1.3 cm2; ***p<0.001). Conclusion Besides the magnitude of deceleration and direction of impact, width and height of the aortic arch are the 3rd and 4th factor directly contributing to the risk of developing traumatic NAAI in severely injured patients.